AFM and SEM Study on Crystallographic and Topographical Evolution of Wet-Etched Patterned Sapphire Substrates (PSS): I. Cone-Shaped PSS Etched in Sulfuric Acid and Phosphoric Acid Mixture (3:1) at 230°C. (1st January 2017) - Shen, Jian; Zhang, Dan; Wang, You; Gan, Yang
Abstract : A thorough understanding about the crystallographic and topographical evolution of wet-etched patterned sapphire substrates (PSS) is essential for revealing the etching mechanism and critical for fabricating optimized PSS for enhanced performance of GaN-based LED devices. As the first one of a series of three papers, using complementary scanning electron microscope (SEM) and atomic force microscope (AFM), we carried out a systematic study on the crystallographic and topographical evolution of cone-shaped PSS etched with an ordinary etchant (H2 SO4 :H3 PO4 = 3:1 at volume ratio, 230°C) which enables crystallographic specific etching. The topography of patterns was found to evolve from normal cones to truncated cones, to triangular pyramids with multiple families of exposed crystallographic planes, then to hexagonal and triangular pyramids with a single family of planes. The Miller indexes of three major exposed crystallographic planes, with decreasing slant angles, were determined to be 1 1 ¯ 0 5, 4 5 ¯ 1 38 and 1 1 ¯ 0 12 with the last two being reported for the first time to our best knowledge. It was clearly demonstrated that AFM, thanks to its 3D topography imaging capability compared to SEM and focused ion beam, can be an indispensable tool for fast and reliable characterization of routine PSS samples.